Recreational trampling impact in Sandakan Rainforest Park (SRP) - K. Ravichandran; Rosmalina Abdul Rashid; Wilter Malandi @ Azwal Aziz; J. K. Lajanga (Faculty of Science and Natural Resources, 2020)
Trampling impact from recreational activities such as hiking may change the physical properties of soil and vegetation growth along the nature trail. This paper aims to identify the effect of nature trail usage on soil and vegetation at Sandakan Rainforest Park (SRP). A total of 30 checkpoints along the trail was identified and three subplots were established at each checkpoint; on the trail, within five metres from the trail and beyond five metres from the trail. Quadrat plots of 1m×1m were placed on every subplot, and soil compaction was measured using a FieldScout SC 900 Soil Compaction Meter. All the readings taken on the plots will be compared to the control plot (undisturbed site). The soil compaction and vegetation abundance between the plots were identified. The paper concludes that the soil compaction, vegetation cover and species diversity in SRFP have been affected by recreational hiking activity.